Edukasi Literasi Digital terhadap Pelaku UMKM Makanan Khas di Kota Palembang - Fajarino, Aldo; Lisanty, Nina; Hamidah, Emmy (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2023)
Along with efforts to increase product sales and income for specialty food of MSME actors in Palembang City, technology and business digitization are urgently needed. This challenge for business people and MSMEs also acts as a good opportunity. Today, the Internet is an effective marketing medium for many consumers. The use of social media is also increasingly widespread as a medium for promotion and online sales. However, the abilities and skills of Indonesian MSME actors in general are still low regarding this digital literacy. Education and training are crucial for increasing this understanding and skills and accelerating the digitalization transformation of Indonesian MSMEs. MSME specialties in Palembang City are mushrooming, considering the many types of specialty foods well-known nationally, such as pempek and its derivatives, various crackers/keeping, various special cakes, and so on. Digital literacy education is carried out for several business people and MSMEs engaged in the specialty food sector in Palembang. The lecture and door-to-door discussions are among the implementation methods for each business participant who previously registered their willingness to participate in this activity. The total participants were as many as 15 businessmen, culinary MSMEs, and specialty foods in Palembang. This training is expected to increase digital literacy among the participating communities and motivate MSMEs to be digitally transformed.